The king of swords : a novel - Stone, Nick, 1966- (London : Penguin Books, 2008)
Investigating a bizarre case in which the victim was found to have ingested a tarot card, Detective Max Mingus and his partner, Joe, follow an increasingly violent trail to a sinister fortune teller and her scheming pimp son.
'First published in Great Britain in 2007 by Michael Joseph'--T.p. verso.
Keywords: Police -- Fiction; Murder -- Investigation -- Fiction; Miami (Fla.) -- Fiction